1999
DOI: 10.1046/j.1365-2958.1999.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple transcription factors of the FNR family in denitrifying Pseudomonas stutzeri : characterization of four fnr‐like genes, regulatory responses and cognate metabolic processes

Abstract: SummaryPseudomonas stutzeri is a facultative anaerobic bacterium with the capability of denitrification. In searching for regulators that control the expression of this trait in response to oxygen withdrawal, we have found an unprecedented multiplicity of four genes encoding transcription factors of the FNR family. The fnrA gene encodes a genuine FNR-type regulator, which is expressed constitutively and controls the cytochrome cbb 3 -type terminal oxidase (the cco operon), cytochrome c peroxidase (the ccp gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…Our data show a phenotype for hemN2 alone, with w nitrate and w nitrite values of Ϫ3.2 and Ϫ3.0, respectively (Table 2). However, hemN4 has previously been reported to encode the functional HemN protein (52), based on genomic proximity to and activation by the O 2 -responsive regulator fnrA/FnrA (Psest_2538), although this was prior to the availability of the P. stutzeri genome sequence (53). We propose that HemN2, not HemN4, is the primary HemN protein in heme biosynthesis.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Our data show a phenotype for hemN2 alone, with w nitrate and w nitrite values of Ϫ3.2 and Ϫ3.0, respectively (Table 2). However, hemN4 has previously been reported to encode the functional HemN protein (52), based on genomic proximity to and activation by the O 2 -responsive regulator fnrA/FnrA (Psest_2538), although this was prior to the availability of the P. stutzeri genome sequence (53). We propose that HemN2, not HemN4, is the primary HemN protein in heme biosynthesis.…”
Section: Resultsmentioning
confidence: 85%
“…For nitrite reduction, we demonstrated that strain RCH2 uses the hemecontaining NirS protein rather than the copper-containing NirK protein under the conditions tested, although it appears that both forms are likely functional. In heme biosynthesis, of the four HemN homologs encoded in the RCH2 genome, HemN2, not the previously proposed HemN4 (52), is the primary heme biosynthesis version. One of three nnrS paralogs in RCH2, nnrS1, is suggested to encode a membrane-bound NO sensor that participates in regulation of NO detoxification.…”
Section: Resultsmentioning
confidence: 92%
“…Since FnrP is not involved in nor regulation but anaerobiosis is still required [201,202], it may be that Nnr has a dual function toward NO and oxygen. This may be also the case for P. stutzeri, for which so far no Fnr-type oxygen sensor-regulator has been found, although this bacterium harbors at least five Crp-Fnr regulators [111,191]. In B. japonicum the signal transduction pathway starts with the hemebased oxygen sensor-regulator system FixLJ.…”
Section: Crp-fnr Superfamily Members As Master Regulators For the Expmentioning
confidence: 87%
“…The Anr regulator affected also anaerobic nitrate denitrification and the existence of recognition sequences specific for a Crp-Fnr regulator thus found its satisfactory explanation [189]. The picture, however, became more complicated when regulatory genes were found on sequencing the regions downstream of the nor operons of P. aeruginosa [190], P. stutzeri [8,191], Pseudomonas sp. G-179 [95] and Pa. denitrificans [118].…”
Section: Crp-fnr Superfamily Members As Master Regulators For the Expmentioning
confidence: 99%
“…10.032 structure of CO-free CooA (inactive for DNA binding) has been solved and a comparison of that structure with the active form of a close homolog, the cAMP receptor protein (termed CRP or CAP), has allowed testable hypotheses to be formed about the mechanism by which CO binding leads to a transcriptionally active form [12][13][14]. These models might also be relevant to other members of the extended CRP family of proteins [15]. (iv) Because CooA is a regulatory protein, it is technically easy to set up an assay system within the cell that allows the ready detection of CooA variants with biochemically interesting properties.…”
Section: Introductionmentioning
confidence: 99%